Habituation of News Text Writing Skills in Elementary Schools through the Journalism Extracurricular Program - Hendrastuti, Mutiara; Rahmawati, Fitri Puji (Universitas Muhammadiyah Surakarta, 2023)
This research aims to analyze journalism extracurricular programs that can develop elementary school student's ability to write news texts. The research used descriptive qualitative methods with a case study strategy. The informants for this research were advisors, class teachers, and students. The results of the research showed that in the planning there is a school principal as the program compiler, the journalism extracurricular advisor have to master 5W+1H and create subject designs; the implementation of the journalism extracurricular program was done using the 5W+1H technique, and the observe, imitate, and modifications technique; the impact of implementing extracurricular journalism programs on students' writing skills increases as shown in their paragraph writing; The obstacles experienced were support from parents, learning motivation, student characteristics; and the solution used is to evaluate student progress at the end of the learning process via the WhatsApp group and accommodate learning styles.. The implications of the results of this research include: 1) school principals can make journalism extracurricular programs into mandatory programs and parents are involved in journalistic activities 2) teachers have to have journalistic skills, and 3) students have to write fluently or participate in journalistic activities more enthusiastically.